"The Land Belongs to Us": Ethnic Claims Over Land During Zimbabwe's Land Reforms. (April 2022) - Chambati, Walter; Mazwi, Freedom
Zimbabwe's radical Fast Track Land Reform Programme (FTLRP), implemented in 2000, diversified the agrarian structure by replacing a few large commercial farms with many smaller-scale farms. In understanding how the allocations evolved, studies have emphasized the effects of class, political party affiliation, gender, citizenship, and generation. However, the influence of ethno-regionalism or ethnicity on land access has been understudied. This article examines how ethnic mobilization structured the results of land distribution on the basis of survey data and other sources. Ethno-regionalism was inevitable in the small-scale A1 farms, since it mainly resettled peasants near their communal areas of origin. However, in the small capitalist A2 farms, ethnic tensions were perceived through exclusions of the "insiders, " as they were edged out of the allocations by the urban middle classes seeking accumulation opportunities in the context of an economic crisis. It is argued that if the latter trajectory persists, demand for land will continue to rise and fuel future land struggles, which might be colored by grievances of prior marginalization along ethnic lines.